Influence of Broken Condition and Instability of the Excavation Site Parameters on the Reliability of the Breakage Face. Issue 2 (1st February 2022) - Bulgakov, A; Evsiukova, A; Kolesnichenko, E
Abstract: This article presents a method for determining the influence of disturbance and instability of the parameters of the excavation site on the reliability of the work of the treatment face. To determine the impact of disturbance and instability of the parameters of the excavation site on the reliability of the treatment face, a method was model for calculating the quantitative and qualitative characteristics of violations. The general assessment of the reliability of the operation of the technological scheme of treatment works in the dredging areas with changing mining and geological conditions is the sum of the partial estimates of its operation in the areas with stable and unstable operating conditions. The change in the readiness coefficient on the disturbed parts of the excavation site is determined, depending on the magnitude of the influence of geological disturbances on the rate of lava movement. The analysis of some results of the problem under study, obtained using the proposed methodology, is given. The dependence was established that the readiness coefficient decreases most intensively at large values of the ratio, and then the intensity of the decrease decreases towards smaller values